MICROSCOPIC AND BIOCHEMICAL BILE STRUCTURE IN ACUTE VIRAL HEPATITIS «C» CONVALESCENT CHILDREN - Fotima Sh. Mamatmusaeva; Akbar R. Reyimbayev; Farzona A. G’ulomova; Nargiza U. Temirova (Central Asian Journal of Medicine, 2024)
We have revealed microscopic and biochemical disorders in the bile of children recovering from acute VHC, namely, the higher levels of mucus and cylindrical epithelium, leucocytoids and crystals that indicate the presence of inflammatory phenomena in the mucous membranes and contribute further to gallstone disease development.